2011
DOI: 10.1093/cid/cir464
|View full text |Cite
|
Sign up to set email alerts
|

Two-Tiered Antibody Testing for Lyme Disease With Use of 2 Enzyme Immunoassays, a Whole-Cell Sonicate Enzyme Immunoassay Followed by a VlsE C6 Peptide Enzyme Immunoassay

Abstract: The 2-EIA strategy matched the individual strengths of the C6 EIA and Western blotting, without the drawbacks. The 2 EIAs provided sensitivity comparable to that of the C6 EIA but maintained the specificity of standard 2-tiered testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
116
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 17 publications
9
116
0
3
Order By: Relevance
“…However, our study was inadequately powered to show a sensitivity benefit of the C6 EIA in early Lyme disease, because only 14% of the serum samples from patients with Lyme disease came from those with solitary EM lesions. In keeping with findings from previous studies [4,7,9,16], we found that the C6 EIA alone was less specific than standard 2-tiered testing. The specificity of a 2-tiered strategy with C6 EIA followed by supplemental immunoblot did not differ from that of standard WCS EIA based 2-tiered testing.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…However, our study was inadequately powered to show a sensitivity benefit of the C6 EIA in early Lyme disease, because only 14% of the serum samples from patients with Lyme disease came from those with solitary EM lesions. In keeping with findings from previous studies [4,7,9,16], we found that the C6 EIA alone was less specific than standard 2-tiered testing. The specificity of a 2-tiered strategy with C6 EIA followed by supplemental immunoblot did not differ from that of standard WCS EIA based 2-tiered testing.…”
Section: Discussionsupporting
confidence: 90%
“…Several previous studies have evaluated the performance of the C6 EIA in adults [4,8,9,14,15]. In the largest study to date, the C6 EIA was evaluated as a stand-alone test in serum samples from 528 well-characterized patients with Lyme disease as well as from healthy blood donors [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations